The school website: Facilitating communication engagement and learning. (27th November 2014) - Taddeo, Carmel; Barnes, Alan
Abstract: School websites are providing education settings with the opportunity to transform and enhance the schooling experience. However, the perceived importance of school websites and the resources invested in developing and maintaining them varies considerably across settings. There is a need to better understand what constitutes an effective website that provides a school with an avenue for delivering innovation in teaching and learning, and complements how a school operates. This study reviewed school websites, specifically how 30 south Australian schools used their website as a teaching learning portal, to support administrative operations and as a marketing platform. Three key questions framed the research. First, what variables should be examined to establish how schools are using their website. Second, what constitutes an engaging and useful school website, and finally what development framework can be devised to assist schools to map their website's strengths and areas requiring further development. The evaluation criteria addressed website design, purpose, content and technology integration. Indicators of progressive and emergent school websites were identified through a deductive content analysis of the websites, which informed a proposed website development framework. The framework and suggested recommendations promote a holistic approach when developing a website to accurately portray a school's identity and effectively address stakeholders' needs.